COLLABORATIVE GOVERNMENT IN PREVENTING SEXUAL VIOLENCE AGAINST WOMEN AND CHILDREN IN WEST JAVA - Hera Widaningsih; Didin Muhafidin; Entang Adhy Muhtar (DIA: Jurnal Administrasi Publik, 2026)
This study explores the implementation of collaborative governance in preventing sexual violence against women and children in West Java Province, Indonesia. Using a descriptive qualitative approach, the research focuses on multi-stakeholder collaboration involving government agencies (e.g., DP3AKB, UPTD PPA), civil society organizations, academics, the private sector, and the media. Data collection methods include literature review, passive observation, semi-structured interviews, and documentation. The analysis employs the interactive model of Miles and Huberman, emphasizing data reduction, display, and conclusion drawing. The findings reveal that although formal regulations such as regional laws and governor decrees exist, practical implementation is still constrained by fragmented coordination, limited trust, and unequal stakeholder participation. DP3AKB functions as a facilitative leader in coordinating various actors, yet challenges remain in institutional design and sustaining a collaborative process. The study concludes that collaborative governance, supported by the Pentahelix model, holds significant potential for advancing preventive strategies, but requires stronger mechanisms for dialogue, trust-building, and inclusive decision-making.